Changes in Inner and Outer Retinal Layer Thicknesses after Vitrectomy for Idiopathic Macular Hole: Implications for Visual Prognosis - Hashimoto, Yuki (PLoS One, 2015)
PURPOSE: To investigate sequential post-operative thickness changes in inner and outer retinal layers in eyes with an idiopathic macular hole (MH). METHODS: Retrospective case series. Twenty-four eyes of 23 patients who had received pars plana vitrectomy (PPV) for the closure of MH were included in the study. Spectral domain optical coherence tomography C-scan was used to automatically measure the mean thickness of the inner and outer retinal layers pre-operatively and up to 6 months following surgery. The photoreceptor outer segment (PROS) length was measured manually and was used to assess its relationship with best-corrected visual acuity (BCVA). RESULTS: Compared with the pre-operative thickness, the inner layers significantly thinned during follow-up (P = 0.02), particularly in the parafoveal (P = 0.01), but not perifoveal, area. The post-operative inner layer thinning ranged from the ganglion cell layer to the inner plexiform layer (P = 0.002), whereas the nerve fiber layer was unaltered. Outer layer thickness was significantly greater post-operatively (P = 0.002), and especially the PROS lengthened not only in the fovea but also in the parafovea (P < 0.001). Six months after surgery, BCVA was significantly correlated exclusively with the elongated foveal PROS (R = 0.42, P = 0.03), but not with any of the other thickness parameters examined. CONCLUSIONS: Following PPV for MH, retinal inner layers other than the nerve fiber layer thinned, suggestive of subclinical thickening in the inner layers where no cyst was evident pre-operatively. In contrast, retinal outer layer thickness significantly increased, potentially as a result of PROS elongation linking tightly with favorable visual prognosis in MH eyes.